The role of author’s programmes in the genres of dialogue on TV - Kumushbibi Rasulovna Ermamatova (Zien Journals, 2022)
Journalism and the media are one of the main intermediaries in communicating with people. Communication is one of the main categories in journalism. There are also certain genres in journalism those are created through dialogue or conversation. These are the genres of interviews and conversations. What genres are being used on television today? Genres such as interviews, conversation, talk shows, debates, how are they differ from each other? What are the differences and similarities between them? By finding answers to these questions, the role and importance of dialogue genres in covering social problems and current issues is understood. On Uzbek TV channels, one can observe the use of dialogue genres in author's programs. Reflection of these aspects can be seen on Russian television. Comparing them, showing the advantages and disadvantages it is received certain conclusions about the influence of the author's performances of this genre on society.
Keywords: television; author’s programme; author; dialogue